Long‐term durability of self‐expanding and balloon‐expandable transcatheter aortic valve prostheses: UK TAVI registry. Issue 5 (15th March 2023) - Ali, Noman; Hildick‐Smith, David; Parker, Jessica; Malkin, Christopher J.; Cunnington, Michael S.; Gurung, Shuslim; Mailey, Jonathan; MacCarthy, Philip A.; Bharucha, Apurva; Brecker, Stephen J.; Hoole, Stephen P.; Dorman, Stephen; et al.
Abstract: Background: With expansion of transcatheter aortic valve implantation (TAVI) into younger patients, valve durability is critically important. Aims: We aimed to evaluate long‐term valve function and incidence of severe structural valve deterioration (SVD) among patients ≥ 10‐years post‐TAVI and with echocardiographic follow‐up at least 5‐years postprocedure. Methods: Data on patients who underwent TAVI from 2007 to 2011 were obtained from the UK TAVI registry. Patients with paired echocardiograms postprocedure and ≥5‐years post‐TAVI were included. Severe SVD was determined according to European task force guidelines. Results: 221 patients (79.4 ± 7.3 years; 53% male) were included with median echocardiographic follow‐up 7.0 years (range 5−13 years). Follow‐up exceeded 10 years in 43 patients (19.5%). Valve types were the supra‐annular self‐expanding CoreValve (SEV; n  = 143, 67%), balloon‐expandable SAPIEN/XT (BEV; n  = 67, 31%), Portico ( n  = 4, 5%) and unknown ( n  = 7, 3%). There was no difference between postprocedure and follow‐up peak gradient in the overall cohort (19.3 vs. 18.4 mmHg; p  = NS) or in those with ≥10‐years follow‐up (21.1 vs. 21.1 mmHg; p  = NS). Severe SVD occurred in 13 patients (5.9%; median 7.8‐years post‐TAVI). Three cases (23.1%) were due to regurgitation and 10 (76.9%) to stenosis. Valve‐related reintervention/death occurred in 5 patients (2.3%). Severe SVD was more frequent with BEV than SEV (11.9% vs. 3.5%; p  = 0.02), driven by a difference in patients treated with small valves (BEV 28.6% vs. SEV 3.0%; p  < 0.01). Conclusions: Hemodynamic function of transcatheter heart valves remains stable up to more than 10 years post‐TAVI. Severe SVD occurred in 5.9%, and valve‐related death/reintervention in 2.3%. Severe SVD was more common with BEV than SEV.